Remifentanil with or without Propofol as Anesthesia Agents for Trans- Vaginal Ultrasonography Oocyte Retrieval (TUGOR) on Pregnancy and Anesthesia Outcomes: A Randomized Controlled Trial - Atashkhoei, Simin; Pouya, Khadijeh; Hakimi, Parvin; Zakeri, Raana; Soltanzadeh, Nasrin; Hatami-Marandi, Pouya (Current Reviews in Clinical and Experimental Pharmacology, 2021)
Background: Transvaginal Ultrasound-Guided Oocyte Retrieval (TUGOR) is a painful procedure, which often requires the application of anesthesia agents. There is a controversy in the literature about the effects of administrated anesthetics for TUGOR on patients & pregnancy outcomes. Objective: The current study aimed to compare the effects of remifentanil with or without propofol, administrated for TUGOR, on pregnancy and anesthesia outcomes. Method: In a double-blind randomized controlled trial, 180 candidates of TUGOR, aged 18-40 years old, were included in the study. All study women received midazolam 0.03 mg/kg and remifentanil 1 ug/kg as anesthesia induction; Later on, they were randomly assigned in two equalsize groups in terms of anesthesia maintenance, as the intervention group received remifentanil infusion 0.25 μg/kg/min and the control group received remifentanil infusion 1ug/kg/min with propofol 50-150 ug/kg/min. Hemodynamic symptoms, operation outcomes, including the side effects, and pregnancy outcomes, were compared between the study groups. The study is registered with the Iranian Clinical Trials Registry, number IRCT201611177013N15. Results: Although the hemodynamic symptoms showed significantly better ranges in the remifentanil group, however, the study groups were not significantly different in durations of operation, anesthesia, and recovery. However, the anesthesia side effects during and after the operation were not significantly different between the groups; they were more common in control one. The reproductive outcomes (numbers of collected oocytes, fertilized oocytes and transferred embryos, pregnancy rates) showed better but non-significant ranges in the remifentanil group. Conclusion: Using remifentanil alone in comparison to remifentanil & propofol in the TUGOR procedure can be achieved better pregnancy outcomes without imposing the side effects of propofol; therefore, it is not recommended to use propofol as an anesthesia agent for a TUGOR procedure.
Keywords: remifentanil